Characteristics of a new type of solid-state electrolyte with a LiPON interlayer for Li-ion thin film batteries - Jee, Seung Hyun; Lee, Man-Jong; Ahn, Ho Sang; Kim, Dong-Joo; Choi, Ji Won; Yoon, Seok Jin; Nam, Sang Cheol; Kim, Soo Ho; Yoon, Young Soo (ELSEVIER, 2010)
In this study, the feasibility of applying lithium phosphorous tungsten oxynitride (Li-P-W-O-N) thin films as solid-state electrolytes in solid-state ionic energy systems such as thin film batteries and super-capacitors was evaluated. The Li-P-W-O-N thin film electrolyte was prepared by radio frequency (RF) magnetron sputtering under various working pressures of nitrogen (N-2) reactive gas. We propose that the LiPON/Li-P-W-O-N/LiPON structure makes it possible to use a Li-P-W-O-N thin film as a thin film solid electrolyte because of the potential short circuiting of the Li-P-W-O-N thin film. To prepare the structure, a LiPON thin film was also deposited by RF magnetron sputtering onto Steel Us Stainless (SUS)/SiO2/Si. When a LiPON thin film interlayer was deposited on the sandwich structure of the Li-P-W-O-N thin film electrolyte, the current was less than 1 mu A. For the final cell structure of SUS/LiPON/Li-P-W-O-N/LiPON/SUS/SiO2/Si, impedance measurements conducted at room temperature revealed ionic conductivities in the range of 1.5-1.2 x 10(-7) Scm(-1) for the various deposition conditions of the Li-P-W-O-N thin films. This result suggests that the LiPON/Li-P-W-O-N/LiPON structured thin film electrolyte has potential as a solid oxide thin film electrolyte in solid-state ionic devices. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: LITHIUM; CONDUCTIVITY; CONDUCTORS; SYSTEM